1996
DOI: 10.1021/tx960085a
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Metabolites of Microcystins Formed in Vivo in Mouse and Rat Livers

Abstract: The hepatic metabolism of microcystins (MCs), potent cyclic peptide hepatotoxins produced by cyanobacteria, was studied by i.p. injection in mice and rats. An immunoaffinity purification method using an anti-MC-LR monoclonal antibody showed a remarkable effect on the removal of contaminants in the hepatic cytosol and enabled us to analyze MCs and their metabolites by HPLC and Frit-FAB LC/MS. At 3, 6, and 24 h post-injection of MC-RR, a small percent of the applied dose was detected in all of the mouse livers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
105
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 21 publications
3
105
0
3
Order By: Relevance
“…Glutathione (GSH), the major non-protein thiol abundant in the cells of most organisms, was demonstrated to play an important role in the detoxification of MCs in both mammals and aquatic organisms (Kondo et al 1996;Pflugmacher et al 1998Pflugmacher et al , 2001He et al 2012;Li et al 2014b). The glutathione and cysteine conjugates of MCs (MC-GSH and MC-Cys) were firstly synthesized under chemical conditions by Kondo et al (1992) with Frit-FAB liquid chromatographymass spectrometry (LC/MS), and then the resulting conjugates were identified as two metabolites of MCs in vivo in the livers of mouse and rat.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione (GSH), the major non-protein thiol abundant in the cells of most organisms, was demonstrated to play an important role in the detoxification of MCs in both mammals and aquatic organisms (Kondo et al 1996;Pflugmacher et al 1998Pflugmacher et al , 2001He et al 2012;Li et al 2014b). The glutathione and cysteine conjugates of MCs (MC-GSH and MC-Cys) were firstly synthesized under chemical conditions by Kondo et al (1992) with Frit-FAB liquid chromatographymass spectrometry (LC/MS), and then the resulting conjugates were identified as two metabolites of MCs in vivo in the livers of mouse and rat.…”
Section: Introductionmentioning
confidence: 99%
“…For MC-LR-GSH, the previous studies primarily focused on the qualitative analyses and no quantitative analyses have been developed [14,28,29]. Kondo et al [28] described the qualitative detection of the metabolites of microcystin-RR and -LR formed in vivo in mouse and rat liver by both HPLC and Frit-FAB LC/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Kondo et al [28] described the qualitative detection of the metabolites of microcystin-RR and -LR formed in vivo in mouse and rat liver by both HPLC and Frit-FAB LC/MS. Pflugmacher et al [14] identified an enzymatically formed glutathione conjugate of the cyanobacterial hepatotoxin MC-LR by HPLC and MALDI-TOF-MS. Ito et al [29] applied an immunostaining method to the study of absorption and distribution of MC-LR and its glutathione conjugate in different tissues in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GSH plays an important role in the detoxification of MCs in aquatic animals. The microcystin-glutathione conjugate has been demonstrated to form via glutathione S-transferase, which appeared to be the first step of detoxification, and then degraded to the cysteine conjugate [10][11][12][13]. However, these studies focused only on qualitative analyses.…”
Section: Introductionmentioning
confidence: 99%